Factors influencing the awareness of University Malaysia Kelantan undergraduate students towards food safety in Pengkalan Chepa - Chin, Chou Yean; Landu, Erna Sarina; Ahmad Anuar, Fatin Nurfarhana; Gan, Yi Peng (2015)
Food safety was a significant concern and very important for each people took seriously on this topic. Nowadays, food safety had been given global awareness due to several occurrences of food poisoning or foodborne illness cases around the world. The objective of this study was investigate the relationship among attitude, on food safety, handling practices and environment concern toward the awareness of the University Malaysia Kelantan (UMK) undergraduate student in Pengkalan Chepa. The study highlighted the awareness of UMK's undergraduate student towards food safety knowledge and practices during food handling to avoid foodborne illness. Total numbers of 200 UMK undergraduate student were the valid respondent for the investigation. According to Pearson correlation, the result proved that attitude of food safety, knowledge of food safety and food handling practices have a positive relationship with the awareness of UMK undergraduate student in Pengkalan Chepa.